Valorization of waste concrete powder as a sustainable substitute for limestone fines in conventional concrete: a case study from Portugal - Ozkan, Hakan (NATURE PORTFOLIO, 2026)
The valorization of industrial by-products in cementitious materials offers a viable pathway for reducing the environmental impact of concrete production. Limestone fines (LF) are commonly used as a filler or a cement replacement material in concrete; however, alternative recycled materials that support circular economy implementation at the industrial scale remain underexplored. This study investigates crushed concrete test sample (CTS) waste, systematically generated during quality-control operations in a ready-mix concrete plant located in Portugal, as a sustainable substitute for LF. CTS powder was used to replace cement at levels of 10-30% in mortar and 10-20% in concrete. Mechanical performance, durability, microstructural characteristics, and environmental impacts were evaluated and benchmarked against LF-containing and reference mixtures. Compressive strength results showed that cement replacement with CTS powder up to 10% produced strength values comparable to both the reference mix and LF-modified mixtures, whereas higher replacement levels resulted in significant strength loss. Durability assessments revealed that both CTS powder and LF at 10% replacement effectively reduced water sorptivity, indicating refinement of near-surface capillary pores, while increased chloride ion penetrability was observed at higher substitution levels. Microstructural analyses (SEM, XRD, and TGA) confirmed that CTS powder acts predominantly as an inert filler, increasing calcite content and promoting early-age nucleation. Life cycle assessment results demonstrated that partial cement replacement with CTS powder can reduce embodied CO2 emissions by up to approximately 17% at a 20% replacement level, with reductions comparable to those achieved using LF.
Keywords: Concrete waste powder; Limestone fines; Cement replacement sustainability; Durability; Circular economy; Science & Technology - Other Topics